The Impact of Andesite Mining Activities on Environmental, Social and Economic Conditions of the Community - Choirunisa, Maria Choirunisa; Muhammad, Fuad; Fahrudin, Fahrudin (Newinera Publisher, 2025)
Mining activities, which play a vital role in fulfilling Indonesia's mineral resource needs, are expected to contribute to the improvement of community welfare. According to Law No. 3 of 2020, the management of mineral and coal resources is aimed, among other objectives, at increasing the income of local communities, regional governments, and the state, as well as creating job opportunities through the implementation of Community Development and Empowerment (PPM) programs. However, in practice, the involvement of mining companies in Semarang Regency remains limited and tends to focus on short-term economic interests that lack sustainability. This study employs a descriptive quantitative method to evaluate the impact of andesite mining activities on the environmental, social, and economic conditions of communities in the ring I area, specifically in Karangjati Subdistrict, Bergas District, Semarang Regency. Data were collected through the distribution of questionnaires to 44 respondents and analyzed using the Likert scale. The research findings indicated that the average scores for the environmental, economic, and social aspects were 3.29, 3.21, and 3.14, respectively. These results suggest that community perceptions of the impacts of mining activities fall within a moderate category. It can be concluded that the community does not perceive significant negative environmental impacts from mining activities, reflecting that the company has carried out environmental management and monitoring (UKL-UPL) optimally, in accordance with environmental quality standards and applicable regulations. In terms of the social aspect, the community tends not to experience noticeable changes as a result of mining operations.